Independent and joint effect of relative telomere length and type 2 diabetes on all-cause mortality in American adults - Lan, Beidi; Bai, Yuan; Chang, Xiaoyi; Zhang, Xiaoxia (Frontiers in Endocrinology, 2022)
Objective: The joint effect of leukocyte telomere length (LTL) and type 2 diabetes (T2D) on the risk of all-cause death has been sparsely explored. The study designed to examine the joint effect of type 2 diabetes and LTL on the probability of death in American adults. Methods: A cohort of 6862 adults with LTL measurements and with or without T2D from the NHANES 1999-2002 with follow-up information until 2015 was studied. Telomere length relative to standard reference DNA (T/S ratio) was measured using qPCR method. Multivariable Cox regression models were used to examine the links between TL and all-cause death possibility using adjusted hazard ratios (HRs). Results: The sample was comprised of adults with an average age of 45.54, and 49.51% males. After a median follow-up period of 14.4 years, 1543 (22.5%) individuals died from all cause. The probability of all-cause mortality was higher among individuals with LTL in the highest tertile than individuals in the lowest tertile (aHR = 0.89; 95%CI: 0.77-1.02); however, the difference did not reach the level of statistical significance (P = 0.096). Conversely, the individuals with type 2 diabetes had a higher probability of death than individuals without (aHR = 1.38; 95%CI: 1.22-1.56; P < 0.0001). When LTL and diabetes status were investigated jointly, subjects in the highest TLT tertile and with diabetes had the highest probability of mortality compared with their counterparts (aHR = 1.47; 95%CI: 1.21-1.77; P < 0.0001). There was a notable and independent effect of low TLT on mortality as demonstrated among individuals with diabetes (aHR = 1.26; 95%CI: 1.09-1.45; P = 0.0015). Conclusion: TLT and diabetes were found to independently and jointly affect the risk of all-cause death. Participants with high TLT and diabetes showed the highest possibility of death compared with other groups.